Respuesta :

Step-by-step explanation:

(a×b^-3×c^-3)⁵ / (a^-3×b⁴×c⁴)^-5

let's look at the numerator (the top) first :

a⁵×b^-15×c^-15

and now the denominator (the bottom) :

a¹⁵×b^-20×c^-20

both divided are (due to the commutative rules of multiplication we can split this first into the parts of the individual variables, and then multiply them all with each other) :

a⁵/a¹⁵ = 1/a¹⁰

b^-15 / b^-20 = b^(-15 ‐ -20) = b⁵

c^-15 / c^-20 = c⁵

so we get as result :

b⁵c⁵/a¹⁰

Answer:

( b^5 c^5 ) / a^10

Step-by-step explanation:

Properties of exponent we are going to use:

First step: [tex]a^{-1}[/tex] = [tex]\frac{1}{a}[/tex]

Second step: [tex]a^{n} b^{n}[/tex] = [tex](ab)^{n}[/tex]

Third step: [tex]a^{m} a^{n}[/tex] = [tex]a^{m+n}[/tex]

Forth step: [tex]( a^{m} )^{n}[/tex] = [tex]a^{mn}[/tex]

~~~~~~~~~~~~~

1). [tex]\frac{( ab^{-3} c^{-3} ) ^{5} }{(a^{-3} b^{4} c^{4} ) ^{-5} }[/tex] = [tex]( a b^{-3} c^{-3} ) ^{5} ( a^{-3} b^4 c^4 ) ^{5}[/tex]

2). [tex]( aa^{-3} b^{-3} b^{4} c^{-3} c^{4} ) ^{5}[/tex]

3). [tex]( a^{1-3} b^{-3+4} c^{-3+4} ) ^{5}[/tex]

4). [tex]a^{-2*5} b^{5} c^{5}[/tex]

[tex]a^{-10} b^{5} c^{5}[/tex] = [tex]\frac{b^5 c^5 }{a^{10} }[/tex]

ACCESS MORE